Sensory optimization of gluten‐free hazelnut omelette and sugar‐modified chestnut pudding: A free choice profiling approach for enhanced traditional recipe formulations - Ortiz‐Solà, J. (2024)
The Mediterranean region is distinguished by its gastronomic diversity and a wide variety of indigenous nut crops. In line with changing global food consumers’ preferences, a noteworthy aspect is the increasing demand to the use of local varieties in recipe formulation. The aim of the present studywas to incorporate the Terra Fria chestnut (Portugal) and Negreta hazelnut from Reus (Spain) in traditional Mediterranean recipes. The sensory, technofunctional, nutritional, and shelf-life characterizationwere investigated in hazelnut omelette (gluten and gluten-free) and chestnut pudding (sugar and sugar-free) formulations. Results conducted by trained assessors using the free choice profiling (FCP) showed that hazelnut omelette samples were described as “creamy,” “smooth,” and “handmade.” In addition, the texture obtained with the hazelnut omelette gluten-free version showed the softest textural profile analysis attributes, with lower values for hardness (2.43 ± 0.36 N), adhesiveness (−0.38 ± 0.00 g s) and gumminess (2.12 ± 0.14). Furthermore, the shelf-life studies revealed a more golden color (>14.43 of a* CIELAB coordinate) and a lower moisture content (25.36%–43.59%) in the hazelnut flour formulation, in addition to the enrichment in terms of protein (8.36 g/100 g), fiber, and healthy fats. In the case of chestnut pudding, it was observed that the study parameters did not differ significantly from its sweetened analogue with positive attributes in FCP (“toasted,” “fluffy,” and “sweet”), positioning it as a viable alternative to sugar in this application. Therefore, both hazelnut flour in hazelnut omelette and oligofructose in chestnut pudding proved to be promising ingredients in the formulation of gluten-free and sugar-free developed products, offering attractive organoleptic and textural characteristics.